Prevalence and determinants of weight misperception in an urban Swiss population (Swiss Medical Weekly, 2016)
AIM: Weight misperception precludes effective management of pre-obesity and obesity, but little is known regarding its status in the Swiss population. Our study aimed to assess the prevalence and determinants of weight over- and underestimation in an adult urban Swiss population. METHODS: Cross-sectional study conducted between 2009 and 2012 in the city of Lausanne. Height and weight were measured using standardised procedures. Weight perception and other socio-demographic variables were collected through questionnaires. RESULTS: Data from 4284 participants (2261 women, 57.5 ± 10.4 years) were analysed. Overall, almost one-fifth (18%) of participants underestimated their weight, while only 7% overestimated it. One quarter of women and half of men with overweight underestimated their weight; the corresponding values for obese subjects were 7% and 10%. Multivariate analysis showed male gender (odds ratio [OR] 3.09, 95% confidence interval [CI] 2.54–3.76), increasing age or body mass index (p-value for trend